Strategic Management Practices In Accreditation And Post-Visitation Phases: A Case Of PKBM Al Ghoutsillah - Muhammad Abduh; Muhammad Yahyadin; Nasri; Rusidah; Aslamiyah (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
This study investigates the institutional management strategies of PKBM Al Ghoutsillah in preparing for and responding to the accreditation visitation process. Employing a qualitative case study design, data were gathered through in-depth interviews, non-participant observations, and document analysis involving seven key informants: the head of the institution, administrative personnel, and senior tutors. Data analysis followed the Miles, Huberman, and Saldaña interactive model, encompassing data condensation, data display, and conclusion drawing. The findings indicate three key dimensions. First, accreditation success was achieved through the effective execution of the POAC management cycle—Planning, Organizing, Actuating, and Controlling. Second, responsive leadership was instrumental in shaping an adaptive organizational culture, promoting collective accountability and institutional flexibility in addressing accreditation feedback. Third, the post-visitation phase demonstrated adaptive crisis management and the strategic use of digital-based documentation systems, facilitating rapid institutional improvement within limited timeframes. Comparative analysis with prior studies on school and madrasah accreditation highlights PKBM Al Ghoutsillah as a best-practice model for non-formal education institutions. Theoretically, this study contributes to the discourse on educational management by elucidating the interrelation between responsive leadership and adaptive culture within the POAC framework. Practically, it offers a replicable model for transforming accreditation from a compliance-oriented procedure into a developmental and sustainable quality assurance mechanism in non-formal education settings.